Job Satisfaction and Associated Factors among Medical Staff in Tertiary Public Hospitals: Results from a National Cross-Sectional Survey in China - Zhou, Huixuan; Han, Xueyan; Zhang, Juan; Sun, Jing; Hu, Linlin; Hu, Guangyu; Wu, Shichao; Zhao, Pengyu; Jiang, Feng; Liu, Yuanli (International journal of environmental research and public health, 2018)
Medical staff in China’s tertiary public hospitals are responsible for providing healthcare to a considerable number of patients, and their job satisfaction needs attention. The aim of this study is to investigate the job satisfaction of medical staff in tertiary public hospitals and to explore its associated factors. Based on a national survey conducted in 2016, this study included 43,645 physicians and nurses nested in 136 tertiary public hospitals in 31 provinces of China. Multi-level logistic regression was used to examine job satisfaction and its association with individual characteristics and job-related factors. Results showed that 48.22% respondents were satisfied with their job, and they were least satisfied with their compensation. Individual characteristics including occupation, gender, education background, alcohol drinking and self-reported health status, as well as job-related factors regarding professional title, work years, income, workload, doctor-patient relationship and practice setting were found to be significantly associated with job satisfaction. Given that some of these factors may be amenable to interventions, we suggest that government and hospital administrators could take some measures to promote continuing education, improve personal health, balance workload and compensation for medical staff, in order to improve the job satisfaction of medical staff in tertiary public hospitals.